Uporządkuj jednomiany:
a) -3*4*(-3¼)*(-3)

b) (-6y)*(-y)*(-0,2)

c) -4*(-x)*(-y)*(-y)*x*y²

d) -2,8a*40ax*(-1)*a²

e) (2½)*x*(-1⅘)*(-10)xy

f) ⅓*a*a*(-b)*a*(-b)*⅓

g) 4xyxyx*x²*y²*x³*y³

h) 0,5xy*5y²x*10x²y

i) -10*(-x)*(-y)*(-x)*(-y)

j) -4²*(-4)²xyx²y²*x³y³

k) -8*x²y²xy

l) (-x)*(-x)*(-15)*(-x)*y²x²y

1

Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-02-16T17:20:44+01:00
A) -3*4*(-3¼)*(-3)=-117

b) (-6y)*(-y)*(-0,2)=-1,2y²

c) -4*(-x)*(-y)*(-y)*x*y²=4x²y⁴

d) -2,8a*40ax*(-1)*a²=42,8a⁴x

e) (2½)*x*(-1⅘)*(-10)xy=45x²y

f) ⅓*a*a*(-b)*a*(-b)*⅓=1/9a³b²

g) 4xyxyx*x²*y²*x³*y³=4x⁸y⁷

h) 0,5xy*5y²x*10x²y=25x⁴y⁴

i) -10*(-x)*(-y)*(-x)*(-y)=-10x²y²

j) -4²*(-4)²xyx²y²*x³y³=-256x⁶y⁶

k) -8*x²y²xy-8x³y³=64x⁶y⁶

l) (-x)*(-x)*(-15)*(-x)*y²x²y =-15x⁵y³
5 4 5